Late Eocene 3He and Ir anomalies associated with ordinary chondritic spinels. (1st May 2017) - Boschi, Samuele; Schmitz, Birger; Heck, Philipp R.; Cronholm, Anders; Defouilloy, Céline; Kita, Noriko T.; Monechi, Simonetta; Montanari, Alessandro; Rout, Surya S.; Terfelt, Fredrik
Abstract: During the late Eocene there was an enigmatic enhancement in the flux of extraterrestrial material to Earth. Evidence comes from sedimentary 3 He records indicating an increased flux of interplanetary dust during ca. 2 Myr, as well as two very large impact structures, Popigai (100 km diameter) and Chesapeake Bay (40–85 km), that formed within 10–20 kyr at the peak of the 3 He delivery. The Massignano section in Italy has one of the best sedimentary records of these events, including a well-defined 3 He record, an Ir-rich ejecta bed related to the Popigai impact event, and two smaller Ir anomalies. Recently we showed that the Popigai ejecta is associated with a significant enrichment of chromite grains (>63 μm) with an H-chondritic elemental composition (17 grains in 100 kg of rock). Most likely these grains are unmelted fragments from the impactor. Slightly higher up (ca. 20 cm) in the section, where a small Ir anomaly possibly related to the Chesapeake Bay impact has been measured, we found a weak enrichment in L-chondritic grains (8 grains in 208 kg of rock). Here we report an extended data set increasing the total amount of sediment dissolved in acid and searched for extraterrestrial chromite grains from 658 to 1168 kg. In altogether 760 kg of background sediment from 17 levels over 14 m of strata outside the interval corresponding to the Popigai and Chesapeake Bay impacts, we only found 2 extraterrestrial chromite grains. Both grains have L-chondritic compositions and were found in a 100 kg sample from the ca. 10.25 m level in the section where the second of the smaller Ir anomalies has been reported. A correlation appears to exist between Ir, 3 He and chromite from ordinary chondrites. We also report oxygen three-isotope measurements of the extraterrestrial chromite grains associated with the Popigai ejecta and confirm an H-chondritic composition. The new results strengthen our scenario that the upper Eocene 3 He and Ir enrichments originate from the asteroid belt rather than the Oort cloud as originally proposed when the 3 He anomaly was discovered. The generally low background concentrations of extraterrestrial chromite through the section speak against any major single asteroid breakup event such as in the mid-Ordovician after the break-up of the L-chondrite parent body. Instead the data reconcile with a small, possibly a factor of 2–3, increase in the flux of extraterrestrial material to Earth, but of both H- and L-chondritic composition. We also report the composition of all the 2310 terrestrial chrome spinel grains recovered, and show that their chemical composition indicates a dominantly regional ophiolitic source. Four anomalous chrome spinel grains with high Ti and V concentrations were found in the Popigai ejecta. These grains originate from Siberian Traps basalts in the Popigai crater at the time of impact.